2014
DOI: 10.1007/s10633-014-9444-z
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal recessive bestrophinopathy associated with angle-closure glaucoma

Abstract: PurposeAbnormalities in the BEST1 gene have recently been recognised as causing autosomal recessive bestrophinopathy (ARB). ARB has been noted to have a variable phenotypic presentation, distinct from that of autosomal dominant Best vitelliform macular dystrophy (BVMD). Both conditions are associated with deposits in the retina, a reduced or absent electro-oculography (EOG) light rise, and the risk of developing angle-closure glaucoma. Herein, we describe the clinical and genetic characteristics of a young mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 31 publications
0
25
0
2
Order By: Relevance
“…Angle-closed glaucoma was observed in 31% (6/20) of the ARB probands, which is lower than the rate (approximately 50%) found in the Caucasian ARB patients. 5,21,35 A recent Japanese study found no ACG in nine patients from seven unrelated families. 31 Currently, only one study has reported four patients with a homozygous mutation p.C251Y in a Chinese family affected with ACG.…”
Section: Discussionmentioning
confidence: 99%
“…Angle-closed glaucoma was observed in 31% (6/20) of the ARB probands, which is lower than the rate (approximately 50%) found in the Caucasian ARB patients. 5,21,35 A recent Japanese study found no ACG in nine patients from seven unrelated families. 31 Currently, only one study has reported four patients with a homozygous mutation p.C251Y in a Chinese family affected with ACG.…”
Section: Discussionmentioning
confidence: 99%
“…[21, 22] Bestrophinopathies caused by BEST1 gene mutations are found to be associated with reduced AL, hyperopia and a high incidence of ACG. [6, 8, 9, 23, 24] Up to 50% of ARB patients are at risk of angle closure glaucoma developing as a result of narrow anterior chamber angles. [6, 14] But the role of bestrophin-1 in the development of ACG has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…[26] Therefore we suspect that the fundal changes of these patients may play a role in the development of postoperative refractory flat anterior chamber. The pre-existed extensive subretinal and intraretinal fluid accumulations, caused by impairment of normal fluid homeostasis by the RPE due to bestrophin-1 dysfunction, [6, 23, 27, 28] may raise pressure difference between the posterior chamber/vitreous cavity and the anterior chamber, especially when filtering exists. This might easily cause forward lens movement and refractory shallow anterior chamber after trabeculectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13][24][25][26][27][28][29] An important clinical component of ARB is its autosomal recessive nature with a BEST1-null phenotype, which makes it a potentially attractive candidate for gene replacement therapy. 12 Unlike ARB, most other diseases ascribed to BEST1 mutations are autosomal dominantly inherited.…”
Section: Discussionmentioning
confidence: 99%